Botulinum toxin in urology - Chancellor, Michael B. 1957-; Smith, Christopher P.; SpringerLink (Online service). (Berlin Springer, 2011)
The minimally invasive use of botulinum toxin (BoNT) in the lower urinary tract has revolutionized the treatment of debilitating bladder, urethra, and prostate conditions refractory to conventional therapy. This is the first book focusing on the practical application of BoNT to the genitourinary tract. An introductory section discusses the biology, pharmacology, and safety of BoNT in the lower urinary tract. Applications of BoNT in the bladder and the prostate and pelvic floor are then covered in detail, with reviews of the latest clinical series and techniques of BoNT injection in both adults and children. The book closes by considering non-genitourinary uses of BoNT and addressing issues of health economics as well as providing insights from experts from across the world. This is a practical, hands-on book that also includes appendices containing easy to read instructions for patients undergoing bladder and prostate BoNT injections and specific nursing procedural issues. The book is written in a concise, uniform, and clinically relevant style by two leading pioneers in the field, Drs. Michael Chancellor and Christopher Smith, who were the first to undertake comprehensive basic research into the mechanisms underlying the efficacy and potential uses of BoNT within the lower urinary tract. Botulinum Toxin in Urology will be of interest to all urologists and urogynecologists who are considering the use of BoNT in their practice.
Safety and General Principles of Botulinum Toxin Therapies: Pearls From Across Medical Fields -- Biology and Mechanism of Action -- Botulinum Toxin for Neurogenic Detrusor Overactivity -- Overactive Bladder and Idiopathic Detrusor Overactivity -- BoNT for Bladder and Pelvic Pain -- Pediatric Botulinum Toxin Applications -- Botulinum Toxin Injection for Prostate Disorders -- Sphincter and Pelvic Floor Disorders Applications -- Non-urological Uses of Toxin with Genitourinary Insight -- Health Economics of Botulinum Toxin Application -- Perspectives from Around the World: Panorama of Where We Are and Where We Are Going.
Electronic reproduction.
Keywords: Botulinum toxin -- Therapeutic use; Medicine; Electronic books